2008
DOI: 10.1159/000163034
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Previous Tracheotomy as a Prognostic Factor in Patients with Locally Advanced Squamous Cell Carcinoma of the Larynx Submitted to Concomitant Chemotherapy and Radiation

Abstract: Hypothesis: The combination of chemotherapy and radiotherapy is a standard nonsurgical treatment for locally advanced laryngeal cancer. Nevertheless, there are no validated markers to predict the outcome of nonsurgical therapies. The impact of previous tracheotomy is not clear in patients submitted to concomitant chemoradiotherapy. Study Design: A non-randomized prospective study. Prognostic factors such as stage, age, performance status, number of chemotherapy cycles, radiotherapy dose, stage VIb disease, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 30 publications
1
24
0
1
Order By: Relevance
“…15 Moreover, PS, 12,16 node invasion 16,17 and localization 12 are prognostic factors for disease-free survival in conjunction with pathologic stage (pT), 17 surgical resection margins 16 and pretreatment tracheotomy. 18 Moreover, T4 primary extension and more than 2 cm tumoral invasion of the base of the tongue were shown to be associated with increased salvage laryngectomy in the Veterans study. 19 …”
Section: Introductionmentioning
confidence: 81%
“…15 Moreover, PS, 12,16 node invasion 16,17 and localization 12 are prognostic factors for disease-free survival in conjunction with pathologic stage (pT), 17 surgical resection margins 16 and pretreatment tracheotomy. 18 Moreover, T4 primary extension and more than 2 cm tumoral invasion of the base of the tongue were shown to be associated with increased salvage laryngectomy in the Veterans study. 19 …”
Section: Introductionmentioning
confidence: 81%
“…Meredith et al [22] suggest irradiation of the pre-existing tracheostomy region. In the literature reports, the recurrence rates in patients who have undergone emergency tracheostomy range between 27% and 71% [7,43,46,47,48]. Prognostic significance of this factor is controversial, as it is most frequently related to higher tumour stage as well as poorer overall performance status of patients and thus may not be an independent prognostic factor.…”
Section: Discussionmentioning
confidence: 99%
“…In the former, the rates differed only marginally in the two treatment groups (total laryngectomy with voice prosthesis and postoperative radiotherapy compared with those receiving concurrent chemoradiation for laryngeal preservation); however, the quality of life score was better in patients treated by chemoradiation [17]. The latter showed that previous tracheotomy was a prognostic factor for a shorter survival time rate (6 vs. 61%); however, as tracheotomy is mandatory in patients with a very advanced tumour stage, the advanced tumour stage is responsible for the poor prognosis [60]. Figure 1 displays the results of all studies where the estimate for 5-year survival is given, together with the result of our meta-analysis using cancer registry studies only [34,35], which yielded an overall rate for 5-year relative survival of 64.2% (95% confidence interval 63.7-64.7%).…”
Section: Combination Of Therapiesmentioning
confidence: 95%
“…Studies evaluating the effectiveness of different therapeutic approaches on survival of laryngeal cancer patients are presented in Table 3 [17,[42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58][59][60]. In the group involving laser surgery, three studies consisted of a mixture of different stages and tumour locations [42][43][44], of which two [45,46] and one assessed advanced laryngeal cancer cases only [47].…”
Section: Laser Surgerymentioning
confidence: 99%
See 1 more Smart Citation